1985
DOI: 10.1128/mcb.5.10.2633
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific RNA metabolism in hepatoma cells: variations in transcription rates and mRNA levels.

Abstract: The transcription rate and abundance of several liver-specific mRNAs as well as mRNAs common to many cel types were compared in a series of rodent hepatoma cell lines, normal liver cells, and primary hepatocyte cultures. The rat hepatoma cell line, Fao, which displays a liver-specific phenotype, contained eight of eight liver-specific mRNAs examined. However, the transcription rates of most liver-specific mRNAs were found to be low (1 to 30%) compared with normal liver in this and other differentiated cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…However, whether the expression of a given gene is controlled in different tissues by distinct regulatory elements and distinct trans-acting regulatory factors is not yet known. Likewise, even though the MUP II, IV, and V mRNAs are processed in the same manner in all tissues, the same species of MUP mRNAs may, in different tissues, exhibit different stability (6,12).…”
Section: Resultsmentioning
confidence: 99%
“…However, whether the expression of a given gene is controlled in different tissues by distinct regulatory elements and distinct trans-acting regulatory factors is not yet known. Likewise, even though the MUP II, IV, and V mRNAs are processed in the same manner in all tissues, the same species of MUP mRNAs may, in different tissues, exhibit different stability (6,12).…”
Section: Resultsmentioning
confidence: 99%
“…This 'minimum deviation' hepatoma cell line has been shown to secrete albumin, to maintain a number of other hepatocyte-specific differentiation markers, and to respond to hormonal stimulation as adult primary hepatocytes (Clayton et al 1985, Lauris et al 1986.…”
Section: Discussionmentioning
confidence: 99%
“…FaO cell line is a well-differentiated liver cell line maintaining a number of hepatocyte-specific markers (Clayton et al 1985, Lauris et al 1986). Cells were grown in Coon's modified Ham's F12 medium supplemented with 10% FBS (Euroclone, Milan, Italy), 100 U/ml penicillin, and 0 .…”
Section: Cell Culturementioning
confidence: 99%
“…Previous studies found a liver-specific hypersensitive site 2.8 kb upstream of the rat albumin promoter (Babiss et al 1986;Turcotte et al 1986;Nahon et al 1987;Tratner et al 1987); this site is in a position similar to the site found at -3.5 kb in mice by Pinkert et al (1987) and in this study. Rodent hepatoma cell lines transcribe the al bumin gene at a much lower rate than liver (Clayton et al 1985b); in such cells the gene is weakly hypersensi tive at the promoter, and not at all at the expected -2.8-kb (Babiss et al 1986;Nahon et al 1987) or -3.5-kb (Y. Bergman and K. Zaret, unpubl. ) sites.…”
Section: Genes and Developmentmentioning
confidence: 99%